Differentiate f = ln(x^2 + 1) / (x ^ 2 + 1).

We'll apply the quotient rule using "u = ln(x2 + 1)" and "v = x2 + 1". First we'll need to calculate u' and v'.Using normal differentiation rules, we can see "v' = 2x". Now the rule for differentiating ln(f(x)) is f'(x) / f(x), so using this we can calculate "u' = 2x / (x2 + 1)".Now we can apply the quotient rule f'(x) = (u'v - uv') / v2 to calculate f'(x). So u'v = (2x / (x2 + 1)) * (x2 + 1) = 2x. And uv' = ln(x2 + 1) * 2x. So f'(x) = (2x - 2xln(x2 + 1)) / (x2 + 1)2.

Answered by William P. Maths tutor

9505 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the radius and centre of the circle given x^2+4x+y^2+2y=20


Find the equation of the tangent to the curve y=x^3-4x^2+2 at the point (3,-7)


integrate from 0 to 2: 2x*sqrt(x+2) dx


Find the coordinates of the stationary points of the curve 3x=y+6x+3


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences